Material concreto y las relaciones lógico matemáticas en niños de preparatoria en la Unidad Educativa Padre Julián Lorente de la ciudad de Loja, periodo 2023-2024 - Cango Cango., Ana Cristina (2024)
Mathematics is fundamental for the intellectual development of children, helping them to reason, be logical and develop mathematical thinking, seeking solutions to the problems of daily life. The objective of this work was to determine how the concrete material strengthens the development of logical-mathematical relationships in high school children at the Padre Julián Lorente Educational Unit in the city of Loja, period 2023-2024. In the development of the research, the quasi-experimental design was used, with a mixed approach to obtain both qualitative and quantitative data and a descriptive scope, likewise the methods were inductive-deductive and analytical-synthetic, allowing the most important information to be selected for the construction of the theoretical framework. Therefore, the observation technique and the Early Mathematical Assessment Test instrument were used to evaluate the level of mathematical components in children aged five to six years, obtaining as results that 65% of the population was in the low, evidencing little knowledge regarding counting, classification, serialization, comparison and identification of basic geometric figures, after the design and application of an activity guide based on the use of concrete material, both structured and unstructured, it was achieved reduce 52% of the difficulties presented in the low zone, ensuring that 60% are located in a moderate zone. It is concluded that the concrete material allowed strengthening the skills of the mathematical components through the manipulation of objects, building their own knowledge through experimentation, since the attention of the children was captured with the attractive materials, motivating them to learn dynamically. and interactive. Keywords: Mathematical component, manipulation, structured material, unstructured material